THE COVID-19: IMPLICATIONS FOR THE ECONOMIC AND RELIGIOUS ACTIVITIES IN PAKISTAN - Abdul Ghaffar; Asim Naeem; Farhan Nazir; Hamid Rasool; Naima Hassan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The outbreak of Covid-19 has taken the entire planet in to its fold, and has caused severe devastation and agony to mankind. This has inflicted grave implications on the cultural, social, religious and economic dimensions, and has changed the way the world operates. Today we dealing with social and economic devastations along with loss of life due to Covid-19 pandemic. This crisis has brought attention to the special value of human life and the revealed inability of States and international organizations to effectively protect it. In this context, there is dire need to explore potential pragmatic solutions in the light of Islamic sources including (but not limited to) Quran verses, teaching and practices of the Prophet Muhammad (SAW); fiqh-ul-hadith; maqasid-e-shariah; and the thoughts of prominent Muslim scholars. The article is conducted through a review of literature in classic and contemporary books and documents such as paper reports. This is a review of economic challenges brought by covid-19 pandemic as well as this paper discusses the help provided by Muslim Scholars to address the issues regarding Islamic ritual practices.